ADding negative pRESSure to improve healING (the DRESSING trial): a RCT protocol. Issue 2 (1st February 2016) - Gillespie, Brigid M; Webster, Joan; Ellwood, David; Stapleton, Helen; Whitty, Jennifer A; Thalib, Lukman; Cullum, Nicky; Mahomed, Kassam; Chaboyer, Wendy
Abstract : Introduction: Obese women are more likely to develop a surgical site infection (SSI) following caesarean section (CS) than non-obese women. Negative pressure wound therapy (NPWT) is increasingly being used to reduce SSI with limited evidence for its effectiveness. Objectives: To determine the clinical and cost-effectiveness of using NPWT in obese women having elective and semiurgent CS. Methods and analysis: A multisite, superiority parallel pragmatic randomised controlled trial with an economic evaluation. Women with a body mass index (BMI) of ≥30, booked for elective and semiurgent CS at 4 Australian acute care hospitals will be targeted. A total of 2090 women will be enrolled. A centralised randomisation service will be used with participants block randomised to either NPWT or standard surgical dressings in a 1:1 ratio, stratified by hospital. The primary outcome is SSI; secondary outcomes include type of SSI, length of stay, readmission, wound complications and health-related quality of life. Economic outcomes include direct healthcare costs and cost-effectiveness, which will be evaluated using incremental cost per quality-adjusted life year gained. Data will be collected at baseline, and participants followed up on the second postoperative day and weekly from the day of surgery for 4 weeks. Outcome assessors will be masked to allocation. The primary statistical analysis will be based on intention-to-treat. Ethics and dissemination: Ethics approval has been obtained from the ethics committees of the participating hospitals and universities. The findings of the trial will be disseminated through peer-reviewed journals, national and international conference presentations. Trial registration number: ACTRN12615000286549; Pre-results.